Effectiveness of yoga on static visual acuity and concentration among male adolescent recurve archers - Karthika, P.; Selvalakshmi, S. (International Journal of Food and Nutritional Sciences, 2022)
The objective of this study was to examine the effectiveness of yoga on the static visual acuity and concentration of male adolescent recurve archers. The experimental and control groups were both investigated. Twenty archers were divided into two groups: ten were allotted to the experimental group, while the remaining ten were assigned to the control group. The participants varied in age from 14 to 17 years old. The yoga intervention was administered to only the experimental group, and static visual acuity and concentration were measured before and after the yoga intervention. The static visual acuity and concentration were evaluated using the snellen chart and concentration grid test, which is a reliable instrument and test for determining the appropriate variable. Using analysis of covariance, the gathered information was statistically examined. Male adolescent recurve archers' static visual acuity and concentration were significantly enhanced following sixteen weeks of yoga practice.